Photodynamic therapy of the surface form of basalioma and actinic keratosis with the topical administration of methyl aminolevulinate - A. A. Kubanova; A. A. Kubanov; I. N. Kondrakhina; N. V. Gribanov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess the efficacy of the photodynamic therapy with the external use of methyl aminolevulinate as a photosensitizer with further irradiation with visible red light with the wavelength of 630 nm in the treatment of patients suffering from a surface form of basalioma and actinic keratosis. Materials and methods. The study involved 28 patients diagnosed with the surface form of basalioma and 34 patients diagnosed with actinic keratosis. They underwent treatment by the photodynamic therapy method using a LED lamp radiating visible red light with the wavelength of 630 nm, with the total dose of irradiation equal to 37 J/cm2. All patients also underwent a confocal in vivo laser scanning microscopy of lesions at the baseline and after 7, 30, 90 and 180 days of treatment. Results. Absolute regression of abnormal lesions was observed in 25 (91%) patients diagnosed with the surface form of basalioma and 30 (88.9%) patients diagnosed with actinic keratosis after 30 days of treatment. No signs of the diseases were revealed in these patients after examination by the method of confocal in vivo laser scanning microscopy. Conclusion. The photodynamic therapy with the local administration of methyl aminolevulinate with further irradiation with visible red light with the wavelength of 630 nm is an efficient method of treatment of the surface form of basalioma and actinic keratosis.